Hidrogeoquímica do aqüífero guarani na área urbana de ribeirão preto (SP) - Conceição, Fabiano Tomazini da [UNESP]; Cunha, Rafael; Sardinha, Diego de Souza [UNESP]; Souza, Antonio Donizetti Gonçalves de; Sinelli, Osmar (My University, 2009)
This work evaluated the hydrogeochemistry of the Guarani Aquifer in the urban area of Ribeirão Preto, São Paulo State. Thirty one sampling points were established and it was carried out field campaigns in 7 and 8 July 2005, analyzing the following parameters: conductivity, temperature, pH, turbidity, color, dry residue, dissolved oxygen, Ca2+, Mg2+, Na+, K+, Fe3+, Al3+, HCO3-, SO42-, PO43-, NO3-, Cl- and F-. The results indicated that the groundwaters in the urban area of Ribeirão Preto pH possess slightly acid, low conductivity, turbidity, color and dissolved oxygen inside the limits established for drinking waters. The ionic composition indicated that the groundwaters have low cations and anions concentration, being they classified as soft water and calcium-bicarbonated. Statistical tests suggested that conductivity and pH are controlled for the calcite dissolution (CaCO3) during the water/rock interaction process. Besides, it is possible to conclude that the high NO3- and PO43- concentrations found in the groundwater in the urban area of Ribeirão Preto are originated due to anthropogenic activities.

Este trabalho avaliou a hidrogeoquímica do Aqüífero Guarani na área urbana de Ribeirão Preto, São Paulo. Trinta e um pontos de amostragem foram estabelecidos e realizaram-se amostragens nos dias 7 e 8 de julho de 2005, analisando-se os seguintes parâmetros: condutividade, temperatura, pH, turbidez, cor, resíduo seco, oxigênio dissolvido, Ca2+, Mg2+, Na+, K+, Fe3+, Al3+, HCO3 -, SO4 2-, PO4 3-, NO3 -, Cl- e F-. Os resultados indicaram que as águas subterrâneas da área urbana de Ribeirão Preto possuem pH ligeiramente ácido, baixa condutividade, turbidez, cor e oxigênio dissolvido dentro dos limites estabelecidos para águas potáveis. A composição iônica indicou que as águas subterrâneas têm baixa concentração de cátions e ânions, sendo elas classificadas como água moles e cálcio-bicarbonatadas. Testes estatísticos sugeriram que a condutividade e o pH são controlados pela dissolução das calcitas (CaCO3) durante o processo de interação água/rocha. Além disso, é possível concluir que as concentrações de NO3 - e PO4 3- encontradas nas águas subterrâneas na área urbana de Ribeirão Preto são originadas devido às atividades antrópicas.
Hydrogeochemistry of the Guarani Aquifer in the urban area of Ribeirão Preto (SP)
Keywords: Anthropogenic activities; Groundwater quality; Water-rock interaction; calcium carbonate; drinking water; human activity; hydrogeochemistry; ionic composition; nitrate; pH; phosphate; sampling; urban area; water quality; water-rock interaction; Guarani Aquifer; South America